The effectiveness of educational interventions on breast cancer screening uptake, knowledge, and beliefs among women: a systematic review - Noman, Sarah; Kadir Shahar, Hayati; Abdul Rahman, Hejar; Ismail, Suriani; Al-Jaberi, Musheer Abdulwahid; Azzani, Meram (MDPI AG, 2020)
There have been various systematic reviews on the significance of educational interventions as necessary components to encourage breast cancer screening (BCS) and reduce the burden of breast cancer (BC). However, only a few studies have attempted to examine these educational interventions comprehensively. This review paper aimed to systematically evaluate the effectiveness of various educational interventions in improving BCS uptake, knowledge, and beliefs among women in different parts of the world. Following the PRISMA guidelines, a comprehensive literature search on four electronic databases, specifically PubMed, Scopus, Web of Science, and ScienceDirect, was performed in May 2019. A total of 22 interventional studies were reviewed. Theory- and language-based multiple intervention strategies, which were mainly performed in community and healthcare settings, were the commonly shared characteristics of the educational interventions. Most of these studies on the effectiveness of interventions showed favorable outcomes in terms of the BCS uptake, knowledge, and beliefs among women. Educational interventions potentially increase BCS among women. The interpretation of the reported findings should be treated with caution due to the heterogeneity of the studies in terms of the characteristics of the participants, research designs, intervention strategies, and outcome measures.